Decision Disparity in Narcotics Abuse - Jumra (Journal of Indonesian Scholars for Social Research, 2023)
This study aims to determine the factors that cause the disparity of decisions in narcotics abuse, as well as how to overcome it. The development of narcotics abuse and trafficking that has hit the world has also affected the country, its development is so rapid that it is very worrying. Indonesia's vast territory and consists of 17 thousand islands in addition to Indonesia's large population of around 250 million, for the narcotics market is an extraordinarily promising market. this is what attracts foreign narcotics mafia to invade Indonesia in various ways. the type of data is primary data and secondary data, primary data obtained through direct interviews with competent respondents. Secondary data is obtained through literature from various books, legal rules, documents, and other written data that are considered related to this research. The results showed that 1) Factors that cause disparity include subjective factors in making decisions as well as aggravating and mitigating factors; 2) Efforts to overcome the disparity in narcotics abuse decisions are to conduct personality development training, in order to be able to demonstrate professionalism and integrity to pay attention to the case at hand, so as to be able to make policies that provide a sense of justice for every community.